Age‐related decrease in periostin expression may be associated with attenuated fracture healing in old mice. Issue 5 (21st September 2022) - Clark, Daniel; Doelling, Jeffrey; Hu, Diane; Miclau, Theodore; Nakamura, Mary; Marcucio, Ralph
Abstract: Older adults suffer more bone fractures with higher rates of healing complications and increased risk of morbidity and mortality. An improved understanding of the cellular and molecular mechanism of fracture healing and how such processes are perturbed with increasing age may allow for better treatment options to manage fractures in older adults. Macrophages are attractive therapeutics due to their role in several phases of fracture healing. After injury, bone marrow–derived macrophages are recruited to the injury and propagate the inflammatory response, contribute to resolution of inflammation, and promote bone regeneration. A tissue resident population of macrophages named osteal macrophages are present in the periosteum and are directly associated with osteoblasts and these cells contribute to bone formation. Here, we utilized bulk RNA sequencing to analyze the transcriptional activity of osteal macrophages from old and young mice present in primary calvarial cultures. Macrophages demonstrated a diverse transcriptional profile, expressing genes involved in immune function as well as wound healing and regeneration. Periostin was significantly downregulated in macrophages from old mice compared to young. Periostin is an extracellular matrix protein with important functions that promote osteoblast activity during bone regeneration. An age‐related decrease of periostin expression was verified in the fracture callus of old mice compared to young. Young periostin knockout mice demonstrated attenuated fracture healing outcomes that reflected what is observed in old mice. This study supports an important role of periostin in fracture healing, and therapeutically targeting the age‐related decrease in periostin may improve healing outcomes in older populations.